Fosfomycin in the Clinical Practice of Urinary Tract Infection - Islam Tariq (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Urinary tract infections (UTIs) are among the most common bacterial infections worldwide, affecting millions of individuals and occurring more frequently in women due to anatomical factors. Specific Background: The increasing prevalence of antimicrobial resistance among uropathogens, particularly Escherichia coli, has complicated conventional treatment approaches and renewed interest in alternative therapeutic agents. Knowledge Gap: Although fosfomycin has gained attention as a treatment option for UTIs, a comprehensive overview of its clinical applications, safety profile, and use in special populations remains important. Aims: This study reviews the role of fosfomycin in the clinical management of UTIs, including its mechanism of action, therapeutic applications, adverse effects, contraindications, and use in pregnant women and pediatric patients. Results: Fosfomycin exhibits broad-spectrum bactericidal activity against Gram-positive and Gram-negative bacteria, including multidrug-resistant pathogens, through inhibition of bacterial cell wall synthesis. Clinical evidence indicates that both single-dose and multiple-dose regimens are utilized according to infection severity and patient characteristics. The drug is generally well tolerated, although gastrointestinal disturbances, electrolyte abnormalities, hypersensitivity reactions, and specific contraindications have been reported. Fosfomycin is frequently recommended for UTIs during pregnancy and has demonstrated utility in pediatric patients, particularly in infections caused by resistant organisms. Novelty: This review consolidates current evidence regarding fosfomycin use across diverse UTI settings, including resistant infections and special patient populations. Implications: Fosfomycin represents a valuable therapeutic option for UTI management in the context of growing antimicrobial resistance and increasing demand for alternative antibacterial therapies. Highlights:• Fosfomycin demonstrates activity against Gram-positive, Gram-negative, and multidrug-resistant uropathogens.• Treatment regimens vary from single-dose administration to repeated dosing based on infection complexity.• Clinical applications include management of UTIs in pregnant women and pediatric populations. Keywords: Fosfomycin, Urinary Tract Infection, Antimicrobial Resistance, Pregnancy, Pediatric Patients